Public-Private Partnerships in the Caribbean Region : Reaping the Benefits while Managing Fiscal Risks - Queyranne, Maximilien; Daal, Wendell; Funke, Katja (Washington, D.C. : International Monetary Fund, 2019)
To provide policymakers in the Caribbean with a governance framework for improving infrastructure through Public-Private Partnerships (PPPs), while limiting their fiscal costs and risks for the government. And to showcase Canada support to FAD technical assistance in the region and FAD collaboration with CARTAC and the Caribbean Development Bank.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet